Sex disparities in adult obesity prevalence across 47 African countries: A cross-sectional descriptive study - Augustus Osborne (PLoS ONE, 2025)
Background Obesity is a growing public health concern in Africa, with evidence suggesting pronounced disparities between men and women. Understanding the prevalence and sex differences in obesity across African countries is critical for informing equity-focused interventions. This study examined the prevalence of adult obesity (body mass index [BMI] ≥30) across 47 African countries using sex-disaggregated data to assess the magnitude of sex disparities in obesity prevalence as a basis for equity-focused public health interventions. Methods This study is a cross-sectional descriptive study using nationally representative, sex-disaggregated data from 47 African countries, primarily for the year 2022, obtained from the World Health Organization Health Equity Assessment Toolkit (HEAT). Adults aged 18 years and older who had recent, available data were included in the study. The primary outcome was the country-level prevalence of adult obesity (body mass index [BMI] ≥30) disaggregated by sex. The secondary outcome was the absolute difference in obesity prevalence between women and men within each country. Results Obesity prevalence among adults varied widely across African countries. South Africa had the highest prevalence at 30.8%, followed by Eswatini (30.1%) and Seychelles (29.4%), while Ethiopia (2.8%), Madagascar (4.3%), and Eritrea (4.8%) reported the lowest rates. Across nearly all countries, women exhibited considerably higher obesity prevalence than men. In South Africa, female obesity prevalence was 45.8%, compared to 13.9% in men a difference of 31.8 percentage points. Large sex disparities were also observed in Eswatini (difference: 28.8), Mauritania (26.1), Lesotho (24.2), Equatorial Guinea (21.8), and Seychelles (19.4). In contrast, only a few countries, such as Burundi, Chad, and Madagascar, showed negligible or slightly higher obesity prevalence among men. Conclusion The findings reveal that adult obesity is a pronounced and growing public health concern in Africa, with marked heterogeneity in prevalence between countries and an overwhelming burden among women. These disparities reflect the sociocultural, economic, and biological factors influencing obesity risk, including urbanization, dietary transitions, and gender norms. The pronounced sex disparity points to the need for context-specific, sex-sensitive interventions and policies to effectively address obesity and its health consequences. Policymakers and health practitioners should prioritize multisectoral strategies that promote healthy diets and physical activity and address the unique barriers faced by women. Enhanced surveillance and research are also needed to further elucidate the determinants of obesity and to monitor progress toward reducing health inequities across the continent, including fiscal, regulatory, and community-based actions tailored to women’s needs.